Subcellular localization and developmental regulation of cytosolic, soluble pyrophosphatase isoforms in Arabidopsis thaliana - Öztürk Gökçe, Zahide Neslihan; Greiner, Steffen; Rausch, Thomas (Turkish journal of botany, 2014)
Pyrophosphate (PPi) is the by-product of several reversible key reactions of primary metabolism. Thus, generated PPi should be removed by hydrolysis via pyrophosphatases to prevent accumulation and to drive anabolism. In plastids, a plastidic, soluble pyrophosphatase splits PPi released by ADPG pyrophosphorylase. The cytosolic PPi pool is believed to be hydrolyzed by tonoplast- and/ or Golgi-integral H+-translocating pyrophosphatases. The Arabidopsis thaliana (L.) Heynh. genome encodes 6 soluble pyrophosphatase isoforms (PPas), 1 of which was shown to be localized in plastids. The remaining 5 of those PPas (PPas 1-5) are more similar to each other with highly conserved protein sequences. They all lack known targeting sequences and are thought to reside in the cytosol. To address their role and redundancy in plants, we performed (i) subcellular targeting of C-terminal PPa:EGFP fusions, (ii) analysis of transgenic promoter β-glucuronidase (GUS) lines to depict differential expression during plant development, and (iii) transcript quantification via real-time PCR to corroborate promoter-GUS data. The results revealed pronounced tissue specificity and developmental regulation for each PPa isoform, but also partial redundancy with coexpression of several PPa isoforms in all plant tissues.
Gesehen am 19.10.2020